Perlindungan Anak Pada Bahaya Gadget - Ode Yahyu Herliany Yusuf; Rosmawati Rosmawati; Febrianti Febrianti; Heryana Mahdani Zahra Ningrum; Sabaria Sabaria; Arwiah Arwiah; Wa Ode Nursukma Ningsih; Salma Salma; Sofia Amalia (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This community service is an effort to increase a positive image about the dangers of gadgets for children and increase parents' attention to children about the dangers of gadgets. This effort will be packaged in the form of community service, in this case protecting children from the dangers of gadgets. The aim of this PKM is to reduce children's addiction to gadgets and change the behavior of those who have been poisoned by gadgets. The methods we use are approach methods and implementation methods. The implementation method includes what impacts are caused by inappropriate use of gadgets, as well as providing understanding to children, including early childhood, to prevent worse things that might occur as a result of excessive use of gadgets in the future. Outcomes It is hoped that this socialization activity will reduce the use of gadgets among children and young children, because they are aware of the negative impacts of gadget use